N-Benzyl-2-(2,4-dichlorophenoxy)acetamide - Chen, Ming-Jun (International Union of Crystallography, 2008)
In the title compound, C(15)H(13)Cl(2)NO(2), the dihedral angle between the aromatic rings is 27.17 (11)°. In the crystal the molecules are linked by N—H⋯O hydrogen bonds.